Ameliorative effect of Berberidis radix polysaccharide selenium nanoparticles against carbon tetrachloride induced oxidative stress and inflammation - Gao, Fei; Liu, Huimin; Han, Hao; Wang, Xin; Qu, Lihua; Liu, Congmin; Tian, Xuemei; Hou, Ranran (Frontiers in Pharmacology, 2022)
Berberidis radix polysaccharide (BRP) extracted as capping agents was applied to prepare BRP-selenium nanoparticles (BRP-SeNPs) in the redox reaction system of sodium selenite and ascorbic acid. The stability and characterization of BRP-SeNPs were investigated by physical analysis method. The results revealed that BRP were tightly wrapped on the surface of SeNPs by forming C-O⋯Se bonds or hydrogen bonding interaction (O-H⋯Se). BRP-SeNPs presented irregular, fragmented and smooth surface morphology and polycrystalline nanoring structure, and its particle size was 89.4 nm in the optimal preparation condition. The pharmacologic functions of BRP-SeNPs were explored in vitro and in vivo. The results showed that BRP-SeNPs could heighten the cell viabilities and the enzyme activity of GSH-Px and decrease the content of MDA on H2O2-induced AML-12 cells injury model. In vivo tests, the results displayed that BRP-SeNPs could increase the body weight of mice, promote the enzyme activity like SOD and GSH-Px, decrease the liver organ index and the hepatic function index such as ALT, AST, CYP2E1, reduce the content of MDA, and relieve the proinflammation factors of NO, IL-1β and TNF-α in CCl4-induced mice injury model. Liver tissue histopathological studies corroborated the improvement of BRP-SeNPs on liver of CCl4-induced mice. The results of Western blot showed that BRP-SeNPs could attenuate oxidant stress by the Nrf2/Keap1/MKP1/JNK pathways, and downregulate the proinflammatory factors by TLR4/MAPK pathway. These findings suggested that BRP-SeNPs possess the hepatoprotection and have the potential to be a green liver-protecting and auxiliary liver inflammation drugs.